DAMPAK PENGGUNAN BRAND AMBASSADOR NCT DREAM TERHADAP MINAT BELI PRODUK MIE INSTAN LEMONILO - Yahya, Maulana Muhammad; Rahman, Yoga Nur; Andayani, Cahyaning; Saputri, Mutiara Audi Malica Ayu; Purwaningsih, Vitriyani Tri; Taher, Arivina Ratih Yulihar (FACULTY OF ECONOMICS AND BUSINESS FLORES UNIVERSITY, 2023)
Abstract Generation Z and millennials are more interested in leading healthy lives. According to Central Agency on Statistics; Statistics Indonesia, 29.94% of Indonesia's population is said to face health issues in 2022. They cannot be distinguished from instant food at the same time. Many healthy food supply companies use this to create appealing products for the general public. One is PT Lemonilo Indonesia Sehat, which releases Mie Lemonilo and advertises it as healthy noodles without the 3Ps (preservatives, artificial colors, and flavors). Along with providing nutritious food items, Lemonilo has partnered with South Korean boyband NCT Dream, whose appealing image is seen to fit with the brand's reputation. This study aims to determine whether NCT Dream's role as a brand ambassador can boost consumers' interest in purchasing Lemonilo goods. Popularity and awards in the form of photo cards were investigated as indicators in this study, while purchase intention was the independent variable. The quantitative method is used in this associative form of research. This study used a simple random sample of 183 respondents from the Twitter base of @nct_menfess between the ages of 15 and 30. The research results show that NCT Dream as a brand ambassador can influence buying interest in the community by 25.23%. At the same time, the rest are other factors outside of research. Keywords: Popularity, Prizes, NCT Dream, Purchase Intention